2016
DOI: 10.1209/0295-5075/113/40008
|View full text |Cite
|
Sign up to set email alerts
|

Measuring lifetime of correspondence with classical decay of correlation in quantum chaos

Abstract: A very weakly coupled linear oscillator is proposed as a detector for observing timeirreversible characteristics of a quantum system, and it is used to measure the lifetime during which a classically chaotic quantum system shows decay of correlation. Except for a particular case where the lifetime agrees with the conventional Heisenberg time, which is proportional to the Hilbert space dimension N , it is in general much longer: the lifetime increases in proportion to the product of N and the number of superpos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…-In the CKR the coupling parameter ǫ sensitively controls its statistical properties. If the standard map with unbounded phase space is used for each KR, the classical chaotic diffusion is recovered as ǫ is increased beyond a threshold proportional to ̵ h. In a previous paper we showed that a similar transition occurs also for bounded finite dimensional CKR and the lifetime of correspondence with classical diffusive behavior is drastically enhanced [14].…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…-In the CKR the coupling parameter ǫ sensitively controls its statistical properties. If the standard map with unbounded phase space is used for each KR, the classical chaotic diffusion is recovered as ǫ is increased beyond a threshold proportional to ̵ h. In a previous paper we showed that a similar transition occurs also for bounded finite dimensional CKR and the lifetime of correspondence with classical diffusive behavior is drastically enhanced [14].…”
mentioning
confidence: 67%
“…which predicts a seemingly strange feature that the lifetime depends on M i.e., the number of eigenstates forming the initial state Ψ 0 ⟩, where Cr 14]. Equation ( 7) explains the numerical results quite well in the fully entangled regime.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…which is nothing more than the temporal absorption rate A τ for z = ν = (Ω − ω) in Eq. ( 6), takes the constant classical value due to the classical chaotic decay of autocorrelation function if τ is less than the "lifetime" τ L [18]:…”
Section: Operation Of the Damper A Energy Transfer Processmentioning
confidence: 99%
“…With the method we can map the Fourier spectral features of correlation function to the diffusion characteristics of a fictious measurement system. Applying the method to coupled quantum chaotic rotors, we found that the time scale on which the decay-able quantum correlation is maintained is proportional to N 2 dim , not N dim if a full entanglement is achieved among the quantum chaos units [18,19]. We called this "lifetime" of the decay-able correlation.…”
Section: Introductionmentioning
confidence: 99%